Ethno-semiotic system of the kazakh yurt (Journal of Philosophy, Culture and Political Science, 2016)
In all traditional cultures, the house has served as an Imago mundi – image of the Universe. No exceptions in this sense the Kazakhs dwelling. It is also a model of the Universe, mediated by the peculiarities of the nomads’ world outlook. There ethno-symbolic system of the Kazakh Yurt is considered in the paper, and it is designated as a national cultural monument. Kazakh people kept the Yurt from an architectural, economic and national position as a product that has no equal, based on life experience.